Analysis of the Influence of Brand Image and Servicescape On Patients’ Repurchase Intention with Hospital Reliability as an Intervening Variable at Sumber Waras Hospital Jakarta - Krisma Kristiana; Rian Adi Pamungkas; Johanes Johanes (International Journal of Nursing and Health Services (IJNHS), 2026)
This study aims to analyze the influence of brand image and servicescape on repurchase intention, with hospital reliability as an intervening variable. The background of this study is based on visit data showing a decline in the number of repeat patient visits at Sumber Waras Hospital as well as increasing competition among hospitals that demands improvement in service quality and trust-based marketing strategies. This study is a quantitative study with a cross-sectional design. Data were obtained through the distribution of questionnaires to 150 respondents who were outpatient consumers of executive polyclinic at Sumber Waras Hospital, Jakarta. The data obtained were analyzed using the Structural Equation Modeling (SEM) method with the assistance of AMOS. The results of the study show that brand image and servicescape have an influence on reliability and repurchase intention. Reliability has an influence on repurchase intention. In addition, reliability can also act as mediating variable between brand image and servicescape. These findings indicate that the better the hospital’s brand image, the better the condition of the physical service environments, and the more reliable the services provided, the higher the consumers’ intention to reuse the services. The practical implication of this study is the importance for the management of Sumber Waras Hospital to strengthen the hospital’s positive brand image, improve the comfort of the physical environment (servicescape), and maintain consistency in providing the best services in order to create consumers repurchase intention that can increase patient loyalty.